Geothermal and Mineralogic Analysis of Hot Springs in the Puracé-La Mina Sector in Cauca, Colombia. (27th February 2019) - Torres-Ceron, Darwin Augusto; Acosta-Medina, Carlos Daniel; Restrepo-Parra, Elisabeth
Abstract : Thermal waters are natural resources of great value to geothermal sciences, the tourism industry, and health. In this work, geochemical classification of physicochemical results of 17 sources at the Puracé-La Mina (Cauca, Colombia) sector was implemented in order to strengthen and determine their potential applications and enhance the continental tourism in Colombia. The analyzed parameters were developed following the Standard Methods 22nd edition, at Universidad Nacional de Colombia-Manizales. According to the results obtained by means of a geochemical classification, it was found that most of the sources have a sulfated-acid nature which makes them heated vapor waters and volcanic waters. Likewise, it was observed that all the sources are immature waters and still do not reach chemical equilibrium. On the other hand, mineralogical and chemical characterization by means of XRD and XRF showed a high content of silica isomorphous minerals with a low concentration. In addition, the presence of Fe2 O3 was observed, which is insoluble at pH > 5 and remains in the rock. Nevertheless, considering that mine sources possess pH ± 2 and temperatures of 40°C, leaching is possible for iron justifying its presence in the water. Instead, elements like Na +, K +, Mg 2+, and Ca 2+ have high mobility at the conditions of mine sources (low pH) as a consequence of hydrolysis processes, which produce variations in water composition.